Analisis Kesalahan Berbahasa pada Teks Opini dalam Website Apakabarnusantara.com Edisi November 2024 sebagai Sumber Bacaan bagi Siswa Kelas XII SMA - Ilma Khalisatul Muntaha; Dhesti Lestari; Linda Selviana; Rahmazeni Ainun Zulfaa; Ana Widya Pratiwi; Asep Purwo Yudi Utomo; Deby Luriawati Naryatmojo; Irfai Fathurohman (BADAN PENERBIT STIEPARI PRESS, 2025)
The use of language in everyday life often goes wrong. Good and correct language use significantly affects a person's reading process. Quality writing adheres to proper linguistic rules. However, many language errors are often found in written texts. This study aims to analyze language errors in opinion texts published in the November 2024 edition of the apakabarnusantara.com website. Another purpose of this study is to evaluate whether the opinion texts on the website are suitable as reading material for 12th-grade high school students, helping them understand proper language use in opinion writing to enhance their language skills. The methods used in this study are qualitative descriptive analysis and a syntactic approach as the theoretical framework. Data were collected by reading several relevant references and recording information that could be used as data. The analysis of this study revealed the use of non-standard words in both texts, such as the word mempengaruhi, which is a common misspelling of the correct form memengaruhi in Indonesian. Both words translate to influence in English, but only memengaruhi is considered standard. Another example includes the use of foreign terms such as best practice. In terms of coherence, the analysis found sentences that introduced new information abruptly, rather than reinforcing the previous ideas. Logical sentence structure was also an issue, as some sentences lacked clarity and failed to convey a clear message to the reader. Additionally, there were ineffective sentences due to the repetition of the same words. This research aims to provide deeper insight into language errors in opinion texts and to promote a better understanding of how to write opinion pieces using correct and appropriate language rules.